UPAYA MENINGKATKAN PERKEMBANGAN BAHASA EKSPRESIF ANAK MELALUI KEGIATAN BERMAIN PERAN “KIDS TRADITIONAL MARKET” DI TK AISYIYAH 57 SURABAYA - ‘Aini, Shofri Qurrotul; Sari, Anisa Yunita (Universitas Narotama, 2023)
This research was carried out with the aim of increasing the development of children's expressive language through role playing activities for kids traditional market at TK Aisyiyah 57 Surabaya. This research method uses classroom action research. Data collection techniques in the form of observation and documentation. Observations were made at TK Aisyiyah 57 Surabaya to obtain data on the development of children's expressive language, documentationin the form of photos of children's activities during learning. The results showed that the development of children's expressive language in children's traditional market role-play activities at TK Aisyiyah 57 can improve children's expressive language, which is included in spoken language where facial expressions, intonation, and body movements can be mixed to support communication. The results obtained from research based on pre-cycle observation data obtained an average learning mastery of 35% or as many as 20 children. In cycle I, children's understanding increased by reaching an average of 65% or as many as 20 children. In cycle II it increased by 75% or as many as 20 children. So it can be concluded that the use of the role playing method with the theme Kids Traditional Market can improve the language development of group B children at Kindergarten Aisyiyah 57 Surabaya. Keywords :Expressive language, Role Playing, Kids Traditional Market